2013
DOI: 10.1007/s10692-013-9453-9
|View full text |Cite
|
Sign up to set email alerts
|

Scientifically substantiated approach to choosing the parameters for forming polymer composites for shell structures

Abstract: 678.046.76 G. V. Lunkina, and V. V. SokolovThis article how the strength properties of polymer composites made by ring winding are affected by the parameters of the production process. Relations are found to connect the contact pressure generated during the formation of the composite with the volumetric content of fibers in its structure. It is shown that the tension on the reinforcing material affects the variation of filament length in the roving. The thickness of the composite is found to influence the unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…4,5 Stokes-Griffin and Compston 6 studied the effect of processing temperature and placement rate on the short beam strength of carbon fibre-PEEK manufactured using a laser tape placement process, and greater rates of cooling were observed at higher placement rates. Yusufov et al 7 discussed the influence of compaction force on the volumetric content, and it was found that the choice made for process parameters had a significant effect on the mechanical characteristics of the finished PCM. Subsequently, some compaction force controllers based on UMAC and fuzzy algorithm were developed to control and monitor the compaction force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Stokes-Griffin and Compston 6 studied the effect of processing temperature and placement rate on the short beam strength of carbon fibre-PEEK manufactured using a laser tape placement process, and greater rates of cooling were observed at higher placement rates. Yusufov et al 7 discussed the influence of compaction force on the volumetric content, and it was found that the choice made for process parameters had a significant effect on the mechanical characteristics of the finished PCM. Subsequently, some compaction force controllers based on UMAC and fuzzy algorithm were developed to control and monitor the compaction force.…”
Section: Introductionmentioning
confidence: 99%
“…Yusufov et al. 7 discussed the influence of compaction force on the volumetric content, and it was found that the choice made for process parameters had a significant effect on the mechanical characteristics of the finished PCM. Subsequently, some compaction force controllers based on UMAC and fuzzy algorithm were developed to control and monitor the compaction force.…”
Section: Introductionmentioning
confidence: 99%